2006
DOI: 10.1111/j.1574-695x.2006.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of complement 3 and mannose receptors in phagocytosis ofParacoccidioides brasiliensisconidia byNramp1congenic macrophages lines

Abstract: Genetic factors influence susceptibility to Paracoccidioidomycosis, a Latin American endemic mycosis. The pattern of susceptibility of congenic mouse strains infected with Paracoccidioides brasiliensis resembles the pattern of the Nramp1 gene. Thus, congenic murine bone-marrow-derived macrophage lines B10R (Nramp1rGly169) and B10S (null Nramp1 protein expression, Nramp1sAsp169) were infected with P. brasiliensis conidia and compared, under opsonic and nonopsonic conditions. Opsonization increased the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The involvement of CR3 and mannose receptor in the uptake of opsonized and nonopsonized P. brasiliensis conidia was documented (Jimenez et al 2006). We have shown previously that mannan can partially inhibit phagocytosis of P. brasiliensis yeasts (da Silva et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The involvement of CR3 and mannose receptor in the uptake of opsonized and nonopsonized P. brasiliensis conidia was documented (Jimenez et al 2006). We have shown previously that mannan can partially inhibit phagocytosis of P. brasiliensis yeasts (da Silva et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Clec1b is able to recognise mannose residues present on the surface of a wide spectrum of microorganisms, including P. brasiliensis [28]. Recently, additional evidence of its importance for the phagocytosis of P. brasiliensis has been obtained by the treatment of macrophages with an analogous methyl-mannoside that reduced the frequency of internalized fungus [29]; in this context, our results are in accordance with this report showing that the up-regulation of Clec1b is probably important for a more effective fungal internalization. Additionally, an induction of other cellular adhesion molecules (ICAM-1, VCAM-1, CD18 and Mac-1) in lungs of mice infected with P. brasiliensis have been observed participating in the inflammatory process and therefore in the pathogenesis of paracoccidiodomycosis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that normal macrophages are permissive to P. brasiliensis growth while cytokineactivated macrophages are able to restrain P. brasiliensis multiplication (22). It was previously demonstrated that C3b, mannose receptor, and gp43, the immunodominant Ag of P. brasiliensis, play an important role in the initial interaction between P. brasiliensis cells and mouse peritoneal macrophages (23)(24)(25). Interestingly, a recent work of our laboratory demonstrated that alveolar macrophages from susceptible mice are easily activated by IL-12 and IFN-␥ and display an efficient fungal killing associated with increased secretion of NO and proinflammatory cytokines.…”
Section: Cd4mentioning
confidence: 99%